2018
DOI: 10.1002/solr.201800248
|View full text |Cite
|
Sign up to set email alerts
|

The Optical Diode Ideality Factor Enables Fast Screening of Semiconductors for Solar Cells

Abstract: In the search for new materials for solar cells, a fast feedback is needed. Radiative efficiency measurements based on photoluminescence (PL) are the tool of choice to screen the voltage a material is capable of. Additionally the dependence of the radiative efficiency on excitation density contains information on the diode ideality factor, which determines in turn the fill factor of the solar cell. Both parameters are immediate ingredients of the efficiency of a solar cell and can be determined from PL measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 59 publications
1
41
0
Order By: Relevance
“…In an aqueous solution, AS ((NH 4 ) 2 S) dissociates into NH 4 + and S 2− and NaS (Na 2 S) dissociates into Na + and S 2− ions. [ 57,58 ] We assume that the S 2− ion diffuses to the surface of the absorber and reacts to fill any anion vacancies. However, the exact sulfur species present in solution depends on the pH, with the more basic NaS‐PDT having a higher proportion of S 2− ions to HS − ions as compared with the AS‐PDT.…”
Section: Discussion: Impact Of S‐salt In S‐pdtmentioning
confidence: 99%
“…In an aqueous solution, AS ((NH 4 ) 2 S) dissociates into NH 4 + and S 2− and NaS (Na 2 S) dissociates into Na + and S 2− ions. [ 57,58 ] We assume that the S 2− ion diffuses to the surface of the absorber and reacts to fill any anion vacancies. However, the exact sulfur species present in solution depends on the pH, with the more basic NaS‐PDT having a higher proportion of S 2− ions to HS − ions as compared with the AS‐PDT.…”
Section: Discussion: Impact Of S‐salt In S‐pdtmentioning
confidence: 99%
“…The same study demonstrated a considerably larger difference between qFLs and V OC in Cu-rich solar cells, indicating that interface recombination poses an additional loss mechanism in Cu-rich Cu(In, Ga)Se 2 . This was confirmed by the investigation of the diode factor in Cu-rich and Cu-poor absorbers and solar cells [24]. In summary: Cu-rich Cu(In, Ga)Se 2 solar cells suffer from interface recombination, but it is not clear why the buffer-absorber interface is different from the one with Cu-poor absorbers.…”
Section: Introductionmentioning
confidence: 94%
“…But quasi‐Fermi level splitting will increase within a diffusion length toward the bulk. Because the higher quasi‐Fermi level splitting leads also to higher luminescence intensity the photoluminescence measurement will detect the higher quasi‐Fermi level splitting in the bulk, whereas V OC is limited by the smaller quasi‐Fermi level splitting at the surface . However, this difference is minimized in absorbers with good transport properties, i.e., long diffusion length, typical for these high efficiency absorbers.…”
Section: Effects Of Post‐deposition Treatment With Heavy Alkalismentioning
confidence: 99%
“…Because the higher quasi-Fermi level splitting leads also to higher luminescence intensity [57] the photoluminescence measurement will detect the higher quasi-Fermi level splitting in the bulk, whereas V OC is limited by the smaller quasi-Fermi level splitting at the surface. [58] However, this difference is minimized in absorbers with good transport properties, i.e., long diffusion length, typical for these high efficiency absorbers. The fact that quasi-Fermi level splitting and open-circuit voltage increase by the same amount upon treatment could hint that the reduction of nonradiative recombination occurs mostly in the bulk of the absorber, not at the surface.…”
Section: Bulk Effectsmentioning
confidence: 99%